Correa Delgado, Rafael Ecuador: de Banana Repúblic a la No Repúblic. Buenos Aires, Debate, 2010, 228 páginas. ISBN: 978–978–1117–88–8. - Vásquez, Juan Pablo (Estudios Avanzados, 2012)
Correa Delgado, Rafael Ecuador: de Banana Repúblic a la No Repúblic. Buenos Aires, Debate, 2010, 228 páginas. ISBN: 978–978–1117–88–8.